Peran Teknologi Perangkat Pembentuk Artificial Intelligence dalam Novel Traveline Past Karya Luna Torashyngu - Muhammad Rasyid Nurrohman; Eva Dwi Kurniawan (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
The aim of this research is to explore the role of Artificial Intelligence (AI) device technology in supporting everyday human life, especially in Luna Torasyngu's novel "Traveline Past." AI is implemented as an intelligent and flexible assistant/partner, serving not only as a mechanical tool but also as an adaptive partner that responds to user needs. Concrete examples include smartwatches, computers with complex authorization systems, sensors that read phenomena and function as weapons, databases encompassing information from the past, and the use of Nano Technology in the production of clothing that can change according to needs. The research findings provide a holistic overview of how AI technology and its related components can shape the lifestyle and interaction of humans with the environment in the future, prompting questions about the positive impact and ethical challenges associated with the integration of AI into daily life. The focus is on analyzing the role of AI-forming device technology in the novel, using a hermeneutic approach. The findings include the utilization of technologies such as 1) smartwatches, 2) computers, 3) sensors, 4) databases, and 5) Nano Technology.